The Metafora Tribhuwana Tunggadewi Jayawisnuwardhani Dalam Diri CEO Wanita - Wiga Purnomo; Noorlailie Soewarno (LPPM dan Fakultas Ekonomi dan Bisnis Universitas Kahuripan Kediri, 2022)
This research metaphorizes the leadership style and characteristics of Tribhuwana Tunggadewi Jayawisnuwardhani that should exist in women when they become CEO. The analysis method is literature studies for obtaining data about Tribhuwana Tunggadewi Jayawisnuwardhani and female CEOs from various sources such as books, websites, journals. The results show that Tribhuwana Tunggadewi Jayawisnuwardhani has transformational leadership style that is very suitable when applied by women when leading. The leadership style combines feminism and masculine. On the feminism side, namely providing support for subordinates to optimize their potential, while on the masculine side, female CEOs can act decisively and wisely.